A face (in) visível da extrema pobreza: experiências de vida no contexto urbano - Vasconcelos, Suziana Martins (2015)
Poverty is defined as a multidimensional syndrome needs in the context of social policies. These dimensions are economic, social and political. The inclusion of social and political dimensions in poverty discussion is intended to incorporate new forms of analysis, that is, beyond the history financial factor. An anti-poverty policy focusing only on insufficient income tends to reinforce the dichotomy between social assistance measures and the direct income transfer programs. The work also has the theoretical framework of reflexive sociology of Pierre Bourdieu, with regard to the concept of misery, i.e. the miserable position in which the point of views of the subjects discuss the condition of each case. These being the conditions conducive to the development of all forms of small misery. In this context, the study has the general objective of understanding the life experiences of individuals in poverty and extreme poverty. However the specific objectives are: to understand the meaning that subjects give the experiences of poverty and (Un) ensure the life story of the excluded subject of government anti-poverty programs. It is a research anchored in the interpretative qualitative paradigm according to Paul Ricoeur's hermeneutics. Depth interviews were conducted with ten individuals in their homes, whose families are in poverty and extreme poverty in two communities of high vulnerability in the outskirts of Fortaleza Ceará. The fieldwork took place from September 2011 to May 2013. The empirical material was subjected to the steps: transcription, textualisation and transcreation, giving rise to ten texts . Each text presents itself the uniqueness of a particular history of the different subjects that deserve different interpretations. These life experiences are discussed with two areas: 1) the life experiences of individuals living in extreme poverty and 2) the invisible face of poverty, which is not achieved by the results socials. The results denounce the various characteristic sufferings of structural poverty and rooted that demand more tan income to overcome it. Thus violence with poverty can be understood as the figure of a spiral, in which curved lines and away from the starting point, does not explain the problem as a ratio of causes and effects. Therefore, the battle waged, in the every day of the life, in the struggle for basic and in defending themselves of the various forms of deprivation and violence, removes all these people the invisible position ordinary people and inserts them in the condition of heroes and extraordinary men.